Aerosol number fluxes and concentrations over a southern European urban area. (15th January 2022) - Casquero-Vera, J.A.; Lyamani, H.; Titos, G.; Moreira, G. de A.; Benavent-Oltra, J.A.; Conte, M.; Contini, D.; Järvi, L.; Olmo-Reyes, F.J.; Alados-Arboledas, L.
Abstract: Although cities are an important source of aerosol particles, aerosol number flux measurements over urban areas are scarce. These measurements are however important as they can allow us to identify the different sources/sinks of aerosol particles and quantify their emission contributions. Therefore, they can help us to understand the aerosol impacts on human health and climate, and to design effective mitigation strategies through the reduction of urban aerosol emissions. In this work we analyze the aerosol number concentrations and fluxes for particles with diameters larger than 2.5 nm measured by eddy covariance technique at an urban area (Granada city, Spain) from November 2016 to April 2018. This is the first study of particle number flux in an urban area in the Iberian Peninsula and is one of the few current studies that report long-term aerosol number flux measurements. The results suggest that, on average, Granada urban area acted as a net source for atmospheric aerosol particles with median particle number flux of 150 × 10 6 m −2 s −1 . Downward negative fluxes were observed in only 12% of the analyzed data, and most of them were observed during high aerosol load conditions. Both aerosol number fluxes and concentrations were maximum in winter and 50% larger than those measured in summer due to the increased emissions from domestic heating, burning of residual agricultural waste in the agricultural area surrounding the site, as well as to the lower aerosol dilution effects during winter. The analysis of the seasonal diurnal variability of the aerosol number concentration revealed the significant impact of traffic emissions on aerosol population over Granada urban area in all seasons. It also shows the impact of domestic heating and agricultural waste burning emissions in winter as well as the influence of new particle formation processes in summer and spring seasons. Closer analysis by wind sector demonstrated that both aerosol concentrations and fluxes from urban sector (where high density of anthropogenic sources is located) were lower than those from rural sector (which includes agricultural area but also the main highway of the city). This evidences the strong impact of aerosol emissions from traffic circulating on the highway on aerosol population over our measurement site. Highlights: Eddy-covariance method was used to evaluate aerosol number fluxes in an urban area. Daily, weekly and seasonal patterns of aerosol flux and concentration were analyzed. The studied urban area acted as a net source for atmospheric aerosol particles. Urban aerosol flux is primarily driven by traffic emissions. Domestic heating and biomass burning significantly impact urban aerosol in winter.